2006
DOI: 10.4321/s0378-48352006000400007
|View full text |Cite
|
Sign up to set email alerts
|

Primary signet-ring cell adenocarcinoma of the urinary bladder: a case report

Abstract: SummaryPrimary signet-ring cell adenocarcinoma of the urinary bladder is a rare tumor. We report in this study the case of a 53 year old man consulting for gross hematuria. Computed tomography imaging demonstrated right hydronephrosis and an invasive bladder tumor. The bladder biopsy showed a signetring cell carcinoma; the exploration of the gastrointestinal tract did nor reveal any other tumor localization. A total cystoprostatectomy was performed followed by adjuvant chemotherapy with cisplatin and gemcitabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…A phase 3 RCT from multi-institutional collaboration in the UK (POUT study), revealed that AC significantly improves disease-free survival and metastasis-free survival compared to surveillance and chemotherapy given at relapse in patients with UTUC [34]. Cobo-Dols M et al [35] and El Ammari JE et al [36] had respectively reported a success case of primary SRCC of bladder treated with radical cystectomy followed by systemic AC with cisplatin and gemcitabine. Considering there is no standard AC strategy for upper urinary tract SRCC, we referenced the chemotherapy for SRCC of urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 3 RCT from multi-institutional collaboration in the UK (POUT study), revealed that AC significantly improves disease-free survival and metastasis-free survival compared to surveillance and chemotherapy given at relapse in patients with UTUC [34]. Cobo-Dols M et al [35] and El Ammari JE et al [36] had respectively reported a success case of primary SRCC of bladder treated with radical cystectomy followed by systemic AC with cisplatin and gemcitabine. Considering there is no standard AC strategy for upper urinary tract SRCC, we referenced the chemotherapy for SRCC of urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Columnar metaplasia of epithelial surface happens with no downward invagination. Predictor variables of such alterations are chronic vesical irritation and infection [ 1 ]. This can be the predisposing factor in the case reported in the present study who underwent cystolithotomy when he was 11 years old.…”
Section: Discussionmentioning
confidence: 99%
“…They performed radical cystectomy with ureterosigmoidostomy (Mainz pouch II) and the patient received adjuvant chemotherapy with cisplatin and fluorouracil following surgery. Cobo-Dols et al [ 1 ] reported a case of PSRCC treated successfully with total cystectomy followed by systemic chemotherapy with cisplatin and gemcitabine, a standard combination for transitional carcinoma of the urinary bladder. Hirano et al [ 10 ] reported success with primary treatment of signet-ring cell adenocarcinoma of the bladder with intra-arterial chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akamatsu et al [1] reported the most commonly used chemotherapeutics utilized in the management of bladder SRC among Japanese institutions to be platinum-based drugs, followed by 5-FU derivatives and anthracycline agents. Cobo-Dols et al [15] utilized a combination of cisplatin and gemcitabine in a patient with pT4aN0M0 SRC of the bladder, with no evidence of disease noted at 8 months posttreatment. The successful use of intraarterial methotrexate and cisplatin with radiation was demonstrated by Ota et al with posttreatment cystectomy revealing no evidence of carcinoma [16].…”
Section: Chemotherapymentioning
confidence: 99%